Playing tennis in the heat - Chappell, A. S. (2001)
Abot playing tennis under heat conditions and how to avoid problems. Playing tennis well in the heat requires extra conditioning. Evaporation through sweating is the body`s only way to cool itself in hot weather. The higher the temperature and humidity the slower sweat evaporates. To compensate the body sweats over a greater percentage of skin surface. The heart must work harder to supply blood to a greater surface area thus necessitating a higher fitness level. A higher level of fitness can be achieved by sweating heavily in practice. Acclimatization to the heat takes 2 weeks and entails enlargement of sweat glands, widening of blood vessels, and conservation of salt. An acclimated athlete loses almost no salt in his sweat or urine. In contrast the amount of potassium excreted in the sweat and urine during hard exercise may be 10 times what it is at rest. Lost potassium must be replaced through the diet to avoid undue fatigue. A well-hydrated athlete will produce copious amounts of clear urine at the start of a match and continue to drink as much as possible during the match. Stomach discomfort and nausea occur only if drinking is delayed until after dehydration has set in. At least one liter of water should be consumed for every kilogram decrease in body weight. Before 1984 the American College of Sports Medicine (ACSM) stated that water was the best fluid for replacement. Since then several studies have shown that carbohydrates and electrolytes should be added to replacement fluid for events longer than one hour. The larger the volume and the cooler and more dilute the drink the faster it will be absorbed. In summary, playing tennis in the heat requires increased fitness which can be attained by sweating heavily in practice over a minimum of 2 weeks. Dehydration can be prevented by eating a well-balanced diet, drinking lots of fluids, and appropriately replacing carbohydrate, electrolyte, and water losses via oral rehydration.